Transmission Dynamics of Recent Outbreaks: Ebola and Zika Virus - Caur, Jasmine (My University, 2017)
The spread of infectious diseases has always been a major cause of misery, sickness and death in humans and animals world-wide. It has caused serious problems for the survival of human beings and other species, and for the economic and social development of the human society. To prevent and to control infectious diseases more effectively, it is important to understand the mechanism of the spread transmission dynamics of the diseases, and then provide useful predictions and guidance so that better strategies can be established. Dynamic modeling of infectious diseases has contributed greatly to this end (Anderson and May, 1991). Dynamical complexity of ecological and epidemiological systems has motivated many researchers to find out the hidden realities of the biological interactions. Epidemiology is now necessary for outbreak investigations, surveillance, hypothesis testing, and generating followup activities necessary to perform a complete and proper epidemiologic analysis. Therefore, mathematical models are designed and explored. In this work, we explore the interplay of infectious diseases and human-animal interactions.
Master of Science -Mathematics & Computing
Keywords: Mathematical Modeling; Epidemiology; Transmission Dynamics; Ebola; Zika